Battery warm-up methodologies at subzero temperatures for automotive applications: Recent advances and perspectives. (March 2020) - Hu, Xiaosong; Zheng, Yusheng; Howey, David A.; Perez, Hector; Foley, Aoife; Pecht, Michael
Abstract: Electric vehicles play a crucial role in reducing fuel consumption and pollutant emissions for more sustainable transportation. Lithium-ion batteries, as the most expensive but least understood component in electric vehicles, directly affect vehicular driving range, safety, comfort, and reliability. However, the overall performance of traction batteries deteriorates significantly at low temperatures due to the reduced electrochemical reaction rate and accelerated health degradation, such as lithium plating. Without timely and effective actions, this performance degradation causes operational difficulties and safety hazards for electric vehicles. Battery warm-up/preheating is of particular importance when operating electric vehicles in cold geographical regions. To this end, this paper reviews various battery preheating strategies, including external convective and conductive preheating, as well as the latest progress in internal heating solutions. The effects of low temperature on batteries from the perspectives of cell performance as well as materials properties are briefly summarized. Thermal science issues involved in warm-up are also elucidated. The framework of battery management systems (BTMS) at low temperatures, including the key design considerations at different battery integration levels and the overall classification of warm-up approaches into external and internal groups, are introduced in detail. Next, a comprehensive literature review on different warm-up strategies is presented, and the basic principles, advantages, disadvantages, and potential improvements of each strategy are elaborated. Finally, future trends of battery warm-up methods are discussed in terms of key technologies, promising opportunities, and challenges.